The Position of Women in Nikah Mut'ah and Milku Al-Yamin Islamic Law and Positive Law Perspectives - Harahap, Nur Sa'adah (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
The practice of mut'ah marriage was one of the patterns of life of the Arab community before Islam came. But it still exists today. Likewise, the concept of milku al yamin has been abolished since the heyday of Islam. However, the practice is still often found today. The practice is called modern slavery. This is very important to be researched because these two practices are no longer relevant to be carried out in the present. This research uses the library research method with data sources of articles, journals, and literature related to nikah mut'ah and milku al yamin. The practice of mut'ah marriage and the concept of milku al yamin that exist today include trafficking in the context of exploitation. This practice puts women in a subordinate position. Even women do not have the share to speak up about their rights in marriage and even in life. So that in the Indonesian context, the practice of mut'ah marriage and milku al yamin has been prohibited because it is a violation of human rights. Positive law and Islamic law uphold human dignity. Humans, both men and women have the same position for Allah. what distinguishes them is only piety.